A case study (I) (Journal of Parents and Teachers, 2014)
This article talks about quality educative intervention to look after the students with special educative needs through a correct diagnose. This articles gives a response to some questions such as how to compensate the students’ deficits and the role of the support programmes, services and resources. The school may reflect about some facts to evaluate the situation and the student and facilitate the resources around to answer to every student’s needs and provide a correct and suitable psycopedagogic intervention.
Keywords: school mediation; cerebral palsy; students with special education needs; integration; psycopedagogic intervention.